PENGARUH TINGKAT KEPUASAN KERJA, BUDAYA ORGANISASI, DISIPLIN KERJA TERHADAP KUALITAS SISTEM INFORMASI AKUNTANSI ERA PADEMI COVID-19 - Asmawati, M.Fadhil Alie (Jurnal Ecoment Global, 2023)
ABSTRACT This study aims to determine the effect of the quality of the accounting information system which is influenced by the level of job satisfaction, organizational culture and work discipline. This study uses primary data distributed via google form to respondents. This research data uses the Structural Equation Model (SEM) method. The population was carried out on MSMEs in Jakarta as many as 250 MSMEs engaged in the sale of clothing. The results of the study show that empirically the variable level of job satisfaction, organizational culture of work discipline has an effect on the quality of accounting information systems. The success of the quality of the accounting information system is the cause of the emergence of a comfortable environment that makes it easier for them to do their work, opportunities and cooperation, in the era of the Covid-19 pandemic which is still so acute.Keywords: Job Satisfaction Level, Organizational Culture, Work Discipline, Quality Accounting Information System